The lower extremity dexterity test quantifies sensorimotor control for cross-country skiing - Krenn, O.; Werner, I.; Lawrence, E.; Valero-Cuevas, F. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Performance in cross-country skiing is mainly determined by the athlete´s physical fitness, gliding skill and equipment. But we lack a scientific understanding, and means to evaluate, the sensorimotor control mechanisms that determine gliding skill. Wellknown balance tasks are discussed to map gliding capability. The aim of this study was to diagnose the meaning of sensorimotor control of force production in the leg for gliding skills in cross-country skiers compared to a one legged balance task.